Reconciling Socrates and Levinas for the Community of Inquiry: A response to Sharp and Laverty (2018) - Emmanuel Skoutas (University of Birmingham Library Services, 2021)
In the publication 'In Community of Inquiry with Ann Margaret Sharp' (2018) the editors, Maughn Rollins Gregory and Megan Jane Laverty present a series of significant essays that honour Anne Margaret Sharp and her significant contribution to the Philosophy for Children (P4C) program. One of the essays, 'Looking at others’ faces' (Sharp & Laverty 2018), is a revised version of Sharp’s earlier essay (see Sharp & Laverty 2018, p. 128, note 2) and further develops her original themes and interests in post-structuralist research and its implications for the P4C program. Sharp and Laverty argue for recognising alterity as informed by Emmanuel Levinas and his notion of the ‘Other’ ('L’Autre') in the Community of Inquiry (CoI) alongside the well-established model of Socratic maieutics. But can Socrates and Levinas be reconciled as Sharp and Laverty invite us? In this essay I examine an interpretation of maieutics from Levinas that makes it both incompatible and yet, ultimately, reconciled with alterity in his notion of teaching. Finally, I explore ambiguities and implications that emerge from accepting this approach and suggest further questions that remain to be explored in relation to the pedagogy of the CoI.